Aspects of teacher training and interlocutions with the teaching initiation program (Research, Society and Development, 2019)
The work presents a research developed with undergraduates of a Teaching Degree in Chemistry, who participated as scholarship holders of the PIBID Project, with the objective of identifying the motivation to choose the undergraduate course, the influence of PIBID on the permanence as a teacher and its impact on the academic formation of the scholarship holders. The methodology was qualitative in nature with interviewing as a form of data collection. The undergraduates emphasized the importance of the methodological proposals developed in the project in their academic formation, and considered the contact with the school reality provided by the PIBID an important aspect for the permanence as teachers. They were surprised to find unattended professionals who encouraged them to give up the teaching career and emphasized the importance of a postgraduate degree as a way to obtain better salaries and professional appreciation.